Designing a system based environmental instruction program and evaluating its effects on seventh grade students - Doğança, Zerrin. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2013., 2013)
The present research aimed to test the effects of an environmental instructional design with systems approach on seventh grade students. The main focus was to examine whether systems approach is a more effective way to teach environmental issues that are dynamic and complex. The research was a quasi-experimental study that enabled to compare performances on general systems thinking skills, competence in dynamic environmental problem solving, and success in standard science achievement tests of subjects from different groups. The sample of the study included 42 seventh grade students (12-14 year old). The same pre, post, and delayed tests were applied to both groups. The control group was taught according to the standard unit plan suggested by the Ministry of Education, while the experimental group was taught the same content with activities including, feedback loops, stock and flow diagrams, behavior over time graphs, and computer modeling. It was found that after one month of systems based environmental instruction, the experimental group performed better on systems thinking skills and dynamic environmental scenarios (DES) tests at .05 significance level. Besides, the effects of the system based intervention were more enduring on performance on DES test for the experimental group, when delayed tests were taken into account. No significance difference was found on science achievement level between the two groups. In addition to quantitative results, interviews resulted in higher levels of feedback thinking skills of the selected respondents from the experimental group.
Keywords: Environmental sciences -- Programmed instruction.